2010
DOI: 10.1042/bc20090132
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of tumorigenesis and oestrogen receptor‐α expression by cell culture conditions in a stem cell‐derived breast epithelial cell line

Abstract: Background information. The common phenotypes of cancer and stem cells suggest that cancers arise from stem cells. Oestrogen is one of the few most important determinants of breast cancer, as shown by several lines of convincing evidence. We have previously reported a human breast epithelial cell type (Type 1 HBEC) with stem cell characteristics and ERα (oestrogen receptor α) expression. A tumorigenic cell line, M13SV1R2, was developed from this cell type after SV40 (simian virus 40) large T-antigen transfecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…The results of this study indicate that continual exposure to DEHP may induce HIF-1α and COX-2 expression and may enhance proliferation ability, which is consistent with previous similar studies (49,50). Elevated expression of inflammatory proteins could elicit various effects, including the promotion of tumor progression, by inducing proliferation and resistance to apoptosis (51). HIF-1α and COX-2 expression was indicated to be increased by DEHP treatment, suggesting that DEHP may serve a critical function in inflammation of human leiomyoma cells.…”
Section: Discussionsupporting
confidence: 80%
“…The results of this study indicate that continual exposure to DEHP may induce HIF-1α and COX-2 expression and may enhance proliferation ability, which is consistent with previous similar studies (49,50). Elevated expression of inflammatory proteins could elicit various effects, including the promotion of tumor progression, by inducing proliferation and resistance to apoptosis (51). HIF-1α and COX-2 expression was indicated to be increased by DEHP treatment, suggesting that DEHP may serve a critical function in inflammation of human leiomyoma cells.…”
Section: Discussionsupporting
confidence: 80%
“…The methods for flow cytometric analysis of gene expression are described in our recent publication (43).…”
Section: Flow Cytometric Analysis Of Gene Expressionmentioning
confidence: 99%
“…However, few major mechanisms have been reported. First, HER2 could regulate cyclooxygenase (COX)-2 [12] and elevated COX-2 could induce many tumorigenic effects such as tumor invasion, angiogenesis, suppression of host immunity, resistance to apoptosis [13-15] and epithelial to mesenchymal transition (EMT) [16]. Second, p185 HER2/neu could phosphorylate and activate major signalling pathways such as phosphatidylinositol-3-kinase (PI3K/Akt) and mitogen-activated protein kinase (MAPK) pathways and promote cell survival, tumor growth and metastasis [10,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…These immortal cells (M13SV1) can be further transformed to weakly tumorigenic (M13SV1R2) and highly tumorigenic cells (M13SV1R2N1) by successive X-ray irradiation and ectopic expression of C-erbB2/neu [28]. Recently, we found that M13SV1R2 cells became non-tumorigenic after growing in a growth factor/hormone-deprived medium for >10 passages (referred to as R2d cells) [16]. Unlike M13SV1R2 cells, these R2d cells contain CD44 + /CD24 - cells previously identified as breast cancer stem cells [29] and were responsive to estrogen for cell growth and tumor development [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation